Granule Leakage Induces Cell-Intrinsic, Granzyme B-Mediated Apoptosis in Mast Cells - Burgener, Sabrina Sofia; Brügger, Melanie; Leborgne, Nathan Georges François; Sollberger, Sophia; Basilico, Paola; Kaufmann, Thomas; Bird, Phillip Ian; Benarafa, Charaf (Frontiers in Cell and Developmental Biology, 2021)
Mast cells are multifunctional immune cells scattered in tissues near blood vessels and mucosal surfaces where they mediate important reactions against parasites and contribute to the pathogenesis of allergic reactions. Serine proteases released from secretory granules upon mast cell activation contribute to these functions by modulating cytokine activity, platelet activation and proteolytic neutralization of toxins. The forced release of granule proteases into the cytosol of mast cells to induce cell suicide has recently been proposed as a therapeutic approach to reduce mast cell numbers in allergic diseases, but the molecular pathways involved in granule-mediated mast cell suicide are incompletely defined. To identify intrinsic granule proteases that can cause mast cell death, we used mice deficient in cytosolic serine protease inhibitors and their respective target proteases. We found that deficiency in Serpinb1a, Serpinb6a, and Serpinb9a or in their target proteases did not alter the kinetics of apoptosis induced by growth factor deprivation in vitro or the number of peritoneal mast cells in vivo. The serine protease cathepsin G induced marginal cell death upon mast cell granule permeabilization only when its inhibitors Serpinb1a or Serpinb6a were deleted. In contrast, the serine protease granzyme B is essential for driving apoptosis in mast cells. On granule permeabilization, granzyme B was required for caspase-3 processing and cell death. Moreover, cytosolic granzyme B inhibitor Serpinb9a prevented caspase-3 processing and mast cell death in a granzyme B-dependent manner. Together, our findings demonstrate that cytosolic serpins provide an inhibitory shield preventing granule protease-induced mast cell apoptosis, and that the granzyme B-Serpinb9a-caspase-3 axis is critical in mast cell survival and could be targeted in the context of allergic diseases.